THE STUDY OF RELIEF PHRASES IN UZBEK LINGUISTICS - B, Farmonov B. (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
This article provides detailed information about the derivatives of nouns from the word relief in the Uzbek language, about their study and classification in Uzbek linguistics. A classification of linguistic studies of relief names in the Uzbek language is proposed. Also, special attention is paid to the importance of studying the semantic structure, historical and etymological features, theoretical and practical issues related to the lexical interpretation of relief names in the Uzbek language.